Subsurface exploration of seabed using electromagnetic waves for the detection of hydrocarbon layers - Ansari, A. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper focuses on the detection of hydrocarbon layers under the seabed using Electromagnetic methods and to prove the relationship between the thickness and resistivity constrast of the hydrocarbon. Simulations have been carried out by varying the depth of seawater from 1000m to 100m and the resistivity contrast and thickness for each level of depth is also varied. The electric field is also measured using various simulation models and graphs over different offsets. The results obtained prove that the resistivity property of Hydrocarbon is directly proportional to the thickness, and at particular points the presence of hydrocarbon layer is clearly significant. Â© 2014 IEEE.